URGENSI PEMIKIRAN IBNU AL-QAYYIM AL-JAUZIYYAH TENTANG PERUBAHAN HUKUM TERHADAP PERKEMBANGAN SOSIAL HUKUM ISLAM DI LINGKUNGAN PERADILAN AGAMA WILAYAH SULAWESI SELATAN - Hj. Rusdaya Basri (DIKTUM: Jurnal Syariah dan Hukum, 2018)
This study examines the urgency of Ibn al-Qayyim al-Jauziyyah's thinking about legal changes to the social development of Islamic law in the Religion Court area of ??South Sulawesi. The thought of Ibn al-Qayyim al-Jauziyyah concerning legal changes to the social development of Islamic law based on changes in time, place, conditions, intentions and customs. Maslahah is the principle to change of legal fatwa based on changes in time, place, circumstances, and customs that apply in a place in accordance with the goals and the benefits desired by the Shari'a. The legal theory of Ibn al-Qayyim al-Jauziyyah in general has been implemented in the ruling or legal stipulation in the Religion Court in the South Sulawesi region. The theory is implicitly used. The judge decides the case with regard to local conditions and conditions.